2018
DOI: 10.7150/jca.23583
|View full text |Cite
|
Sign up to set email alerts
|

Survival Outcomes for Patients with Surgical and Non-Surgical Treatments in Stages I-III Small-Cell Lung Cancer

Abstract: Objectives: Chemotherapy and radiation therapy are the standard treatments for patients with small-cell lung cancer (SCLC). However, recent studies suggest that patients with limited stage (I-III) SCLC may benefit from surgical treatment. This study was performed to evaluate the survival outcomes of surgery for stage I-III SCLC.Methods: This analysis used data from the Surveillance, Epidemiology, and End Results (SEER) database. All stage I-III (excluding N3 and Nx) SCLC patients received a diagnosis between 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 35 publications
0
32
1
Order By: Relevance
“…The NCCN guidelines version 2 (2018) suggest that patients with SCLC at a stage higher than T1-2 with N0 do not benefit from surgery 6 . However, reports show that surgery can Ivyspring International Publisher significantly improve survival outcomes in SCLC patients and should be considered in the management of SCLC at stages higher than T1-2 with N0 7 .…”
Section: Introductionmentioning
confidence: 99%
“…The NCCN guidelines version 2 (2018) suggest that patients with SCLC at a stage higher than T1-2 with N0 do not benefit from surgery 6 . However, reports show that surgery can Ivyspring International Publisher significantly improve survival outcomes in SCLC patients and should be considered in the management of SCLC at stages higher than T1-2 with N0 7 .…”
Section: Introductionmentioning
confidence: 99%
“…We divided the 15 articles into 21 studies because 5 articles were straight stratified according to surgical treatment type or clinical stage [14, 19, 21, 3031]. HRs were extracted directly for 7 out of 15 studies [11, 1417, 2021], and calculated using the Kaplan-Meier curve for the remaining. Significant statistical difference was observed between the surgery and NST groups in a pooled analysis of OS for 41,297 patients from retrospective studies (HR = 0.56, 95% CI: 0.49–0.64, P < 0.001) (Fig 2A), but not for 186 patients from RCTs (HR = 0.77, 95% CI: 0.32–1.84, P = 0.55) (Fig 2B).…”
Section: Resultsmentioning
confidence: 99%
“…However, these RCTs were performed more than 2 decades ago, which from today’s perspective, did not fulfil modern quality requirements. Recent data from numerous retrospective studies, including some large retrospective cohort studies, have demonstrated a potential survival benefit from surgery in patients with limited disease [1121]. In light of these findings, we carried out a systematic review and meta-analysis of the currently available evidences to further determine whether surgery-based multi-modality treatment improves survival when compared to RT, chemotherapy, or a combination of both in patients with stage I to III SCLC.…”
Section: Introductionmentioning
confidence: 99%
“…When the two had different opinions, the third radiologist reviewed them. The TNM staging criteria for patients were based on the Union for International Cancer Control/American Joint Committee on Cancer (UICC/AJCC) 8th Edition (34,35). The inclusion criteria were: 1) 18-75 years old and KPS score ≥ 70; 2) lung cancer diagnosed by histopathology; 3) no EGFR/ALK mutations; 4) if EGFR/ALK mutation, patients must have received EGFR/ALK-TKIs as rst-line treatment, and exhibited resistance or intolerance; 5) received at least two chemotherapy regimens or intolerance, 6) BM was diagnosed by computed tomography/magnetic resonance imaging (CT/MRI); 7) patients received CRT and anlotinib concurrent treatment, or CRT treatment alone (Fig.…”
Section: Patientsmentioning
confidence: 99%